An analysis of code mixing in Twitter used by English department students at University - Pratama, Cintia; Purwanti, Indah Tri; Masyhur, Masyhur (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aimed to identify and analyze the types and functions of code mixing used by English department students at Universitas Riau in their Twitter accounts. Using a qualitative descriptive research design, 63 students from the classes of 2018, 2019, and 2020 were selected through purposive sampling. Data was collected through observation and documentation techniques, and analyzed using Hoffmann’s (1991) and Poplack’s (1980) theories to determine the types of code mixing, and Hoffmann (1991), Saville-Troike (1986), and Holmes (2013) theories to identify the functions of code mixing. The findings showed that most students used Indonesian as the base language and frequently used intra-sentential code mixing, particularly the most basic form involving words and phrases. The function of emphasis was the most common, highlighting the need for students to be more critical in choosing appropriate vocabulary in their tweets. These findings suggest the importance of considering sociolinguistic factors in language education.